"The home isn't like a safe space for them"—Ideals of home and family relationships in children's talk about family adversity and help‐seeking. (26th June 2022) - Spånberger Weitz, Ylva
Abstract: The aim of this study is to explore how schoolchildren reflect on children's help‐seeking in the context of family adversity after participating in lessons about the child welfare services. A thematic narrative analysis was conducted, building on participating pupils' shared reflections on a fictitious story about two siblings living in adverse family circumstances. The analysis suggests that the pupils held a strong belief on children's rights to a safe home with supportive parental relationships, and they expressed an optimistic view on children's opportunities to receive help to achieve positive change when their rights regarding these issues were not met.